G-Supplemented Modules - Koşar, B.; Nebiyev, C.; Sökmez, N. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
Following the concept of generalized small submodule, we define g -supplemented modules and characterize some fundamental properties of these modules. Moreover, the generalized radical of a module is defined and the relationship between the generalized radical and the radical of a module is investigated. Finally, the definition of amply g -supplemented modules is given with some basic properties of these modules.